Effect of Catch and Labor Burden on Fishermen's Income in Pauh Village Moro District Karimun Regency - Hadli Lidya Rikayana; Susilawati (Journal of Research in Business, Economics, and Education, 2021)
This research was conducted in Pauh Village, Moro District, Karimun Regency, which aims to determine the factors that affect the income of fishermen in Pauh Village. This study uses a quantitative approach with multiple linear regression models. The number of fisherman samples used were 32 fishermen. The sampling technique was carried out by purposive sampling. The results showed that partially the catch and labor load affected the income of fishermen in Pauh Village, Moro District, Karimun Regency, and simultaneously the catch variable and labor load influenced the fishermen's income in Pauh Village, Moro District, Karimun Regency.